Analysis of the Use of SiBakul Jogja to Increase the Competitive Value of MSMEs Businesses in Jogja Province - Solihah, Ulfa Maratus; Bambang Septiawan (Indonesian Journal of Economic & Management Sciences, 2024)
This study examines "SiBakul Jogja" as an electronic market platform to boost Jogja MSMEs' competitiveness. The qualitative research method involves document analysis to retrieve relevant data from numerous papers. This approach involves collecting data from papers, books, journals, and notes without research subjects' participation. According to research, “SiBakul Jogja” boosts brand visibility, market reach, and MSMEs' business training. Seller competition and stock management are challenges. This study advises MSMEs on using e-market platforms to succeed in the digital age. This report helps illustrate how "SiBakul Jogja" helps MSMEs compete and overcome growing business complexity